Running economy of African and Caucasian distance runners - Weston, A. R.; Mbambo, Z.; Myburgh, K. H. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Anecdotal evidence suggests an advantageous physiological endowment of the African endurance athlete. Higher fractional utilization of V(dot)O2max has been suggested but not measured directly, and investigations of running economy have been inconclusive. The aim of the current study was to measure a) running economy and b) fractional utilization of V(dot)O2max, in African and Caucasian 10-km runners of similar body mass. Methods: Eight African and eight Caucasian runners had no significant difference in mean race time (32.8 ± 2.8, 32.0 ± 2.5 min, respectively), body mass (61.4 ± 7.0, 64.9 ± 3.0 kg), age, body fat, or lean thigh volume. Caucasian runners were 6 cm taller (P < 0.05). Subjects completed a progressive treadmill V(dot)O2peak test. On a separate day, subjects completed two 6-min workloads (16.1 km·h-1 and 10-km race pace) separated by 5 min. Results: Mean V(dot)O2peak was 13% lower in the Africans (61.9 ± 6.9, 69.9 ± 5.4 mL·kg-1·min-1, P = 0.01). At 16.1 km·h-1, the Africans were 5% more economical (47.3 ± 3.2, 49.9 ± 2.4 mL·kg-1·min-1, P < 0.05). This difference increased to 8% (P < 0.01) when standardized per kg0.66. At race pace, the Africans utilized a higher %V(dot)O2peak (92.2 ± 3.7, 86.0 ± 4.8%, P < 0.01) and had higher HR (185 ± 9, 174 ± 11 b·min-1, P < 0.05) and plasma [ammonia] (113.2 ± 51, 60.3 ± 16.9 µmol·L-1, P < 0.05). Despite the higher relative workload, the plasma [lactate] was not different (5.2 ± 2.0, 4.2 ± 1.7 mmol·L-1, NS). Conclusions: This study indicates greater running economy and higher fractional utilization of V(dot)O2peak in African distance runners. Although not elucidating the origin of these differences, the findings may partially explain the success of African runners at the elite level.